Factors that contribute to HIV and AIDS stigma among nurses at the Polokwane-Mankweng Hospital Complex in the Limpopo Province, South Africa - Kgosimore, Kenalemang Cynthia (My University, 2016)
Purpose of study: The purpose of this study was to determine the factors that contribute to HIV and AIDS stigma amongst nurses at the Polokwane-Mankweng Hospital Complex in Limpopo Province, South Africa. Objectives: The objectives of this study were to identify the sources of stigma at the health facility, to determine whether attitudes, beliefs, and knowledge contribute to HIV and AIDS stigma, and to develop intervention programmes to reduce HIVrelated stigma. Method: A descriptive cross sectional survey using self-administered questionnaire was used in this study to describe factors that contributed to HIV and AIDS stigma. Data collection: The researcher collected data by means of a structured questionnaire and analysed the results with the assistance of the Statistical Package for Social Sciences (SPSS) software program. Results: The study revealed that negative attitudes and a lack of knowledge contributed to AIDS-related stigma. The study recommended that any stigma reduction programme should be implemented at three levels; namely at the individual, environmental, and policy levels. Conclusion: Fear of infection and lack of knowledge about HIV and AIDS fuel negative attitudes towards people living with HIV and AIDS. Education and training are necessary to mitigate stigma.
Thesis (MPH.) -- University of Limpopo, 2016
Keywords: HIV and AIDS; HIV and AIDS stigma; HIV (Viruses); HIV-positive persons; Nurses -- Attitudes; AIDS (Disease) -- South Africa -- Limpopo